2003
DOI: 10.1196/annals.1299.041
|View full text |Cite
|
Sign up to set email alerts
|

NF‐κB Inhibition Restores Sensitivity to Fas‐Mediated Apoptosis in Lymphoma Cell Lines

Abstract: Failure to perform the Fas-related apoptosis pathway can account for tumor resistance both to chemotherapeutic agents and to immunological effectors. We studied the role of NK-kappaB in Fas-resistance, employing the Fas-sensitive human T-lymphoma HuT78 cell line and its Fas-resistant variants HuT78B1 and HuT78G9. All these cell lines expressed high levels of constitutively activated NF-kappaB. Pretreatment of cells with NF-kappaB inhibitors (PDTC, MG132, or SN50) strongly enhanced CH11-induced apoptosis in HuT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Our results demonstrate that lymphoma cell lines with NF-B-ca exhibited very limited induction of apoptosis through either the intrinsic or extrinsic pathways, in comparison to cells lacking NF-B activity. These results confirm and extend previous results (36)(37)(38)(39)(40). We also showed that the inhibition occurred early in the activation of both apoptotic cascades, because there was no apparent reduction in caspase 8 or 9 levels.…”
Section: Discussionsupporting
confidence: 93%
“…Our results demonstrate that lymphoma cell lines with NF-B-ca exhibited very limited induction of apoptosis through either the intrinsic or extrinsic pathways, in comparison to cells lacking NF-B activity. These results confirm and extend previous results (36)(37)(38)(39)(40). We also showed that the inhibition occurred early in the activation of both apoptotic cascades, because there was no apparent reduction in caspase 8 or 9 levels.…”
Section: Discussionsupporting
confidence: 93%
“…While we showed the NFκB activation, there was no change in apoptosis after inhibition of the NFκB pathway with SN50. Thus, inhibition of NFκB activation alone may not translate into an effective anti-apoptotic response in childhood ALL as it does in other malignancies [25][26][27].…”
Section: Discussionmentioning
confidence: 88%
“…Recently, researchers have shown that inhibition of NF-nB activity restores sensitivity to Fas-mediated apoptosis (43,44). Treatment of breast cancer cells with Ad-MMP-9, radiation, or both induced caspase-dependent apoptosis, which is associated with the activation of several individual caspases.…”
Section: Discussionmentioning
confidence: 99%